Analisis pengaruh koefisien konveksi media pendingin terhadap temperatur panel surya dengan perendaman sebagian (Partially Submerged Photovoltaic) - Rijal Surya Rahmany; I Made Ivan Wiyarta Cakra Sujana; Yongki Christandi Batubara (Universitas Muhammadiyah Metro, 2026)
One of the main challenges in PV system deployment is the increase in panel operating temperature, which leads to a reduction in energy conversion efficiency, particularly in tropical regions with high solar irradiance. Potential solution to mitigate this issue is the partially submerged photovoltaic (PSPV) system. This study aims to analyze the influence of convective heat transfer coefficients on the surface of a PSPV system on the operating temperature of photovoltaic panels using a numerical modeling approach. The research methodology involves the development of an energy balance model that accounts for the contributions of solar radiation, convective heat transfer, and thermal radiation. The panel area is divided into two equal sections with a 50:50 ratio, consisting of a submerged portion and an air-exposed portion. The convective heat transfer coefficients for the submerged section are set to 100 W/m²K for both the upper and lower surfaces. For the air-exposed section, the upper surface convective heat transfer coefficient is varied between 10 and 70 W/m²K, while the lower surface coefficient is maintained at 10 W/m²K. Simulation results indicate that the presence of water as a cooling medium significantly reduces the panel operating temperature to approximately 31 °C, compared to a fully air-exposed panel configuration, which reaches an operating temperature up to around 55 °C.